Potato peel starch efficiency as a coagulant for removing physicochemical parameters from the locumba river in tacna, peru (Journal SCIENCEVOLUTION, 2024)
Water pollution is a serious environmental problem affecting many cities around the world. This has prompted the development of more economical and sustainable treatment methods. In this study, the effectiveness of potato peel starch as a coagulant to reduce certain physicochemical parameters was evaluated in the Locumba River, in Tacna. 5 kg of potatoes of the canchan variety were washed, peeled and cut into pieces, then subjected to 100 °C for two hours. The potatoes were then mashed and filtered to obtain the starch. The coagulant solution was prepared by stirring at 1000 rpm for 30 minutes on a magnetic stirrer to achieve uniform mixing. 600 ml of the solution was transferred to different containers with concentrations of 25 mg/l, 50 mg/l and 75 mg/l. The results indicated that, when applying a dose of 75 mg/l and using the Tukey method with a 95% confidence level, an 88.85% reduction in turbidity was achieved. In addition, there were minimal changes in the pH of the water treated with the potato peel coagulant. It was concluded that increasing the amount of natural coagulant improves the effectiveness in reducing turbidity in wastewater.
Keywords: Potato skin; Turbidity; Removal; Natural coagulant